Developing strategic relationships for religious tourism businesses: a systematic literature review. (2017) - Heidari, Ali; Yazdani, Hamid Reza; Saghafi, Fatemeh; Jalilvand, Mohammad Reza
The purpose of this paper is to systematically analyse the existing literature on the interrelationships of tourism businesses in the context of religious tourism. By taking a systematic approach to literature review, a total of 34 academic articles was content analysed. As a general framework, Watkins and Bell's classification was applied in order to increase the review consistency and validity. The results show that the inter-relationships of tourism businesses have gained increasing academic attention in the past decade in terms of the number of published articles. The various categories of inter-organisational relationships often used in relation to tourism business setting are explored. The timeline of business relationships research in tourism literature are presented along with a methodological approach to the literature. The most of existing articles claim to study the cooperative relationships of tourism businesses. The main methodological approach used in studying inter-organisational relationships of tourism businesses was empirical one.